2015
DOI: 10.1371/journal.pone.0127802
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Inhibits Escherichia coli ATP Synthase and Cell Growth

Abstract: We examined the thymoquinone induced inhibition of purified F1 or membrane bound F1FO E. coli ATP synthase. Both purified F1 and membrane bound F1FO were completely inhibited by thymoquinone with no residual ATPase activity. The process of inhibition was fully reversible and identical in both membrane bound F1Fo and purified F1 preparations. Moreover, thymoquinone induced inhibition of ATP synthase expressing wild-type E. coli cell growth and non-inhibition of ATPase gene deleted null control cells demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 55 publications
6
41
0
Order By: Relevance
“…Double mutants αI346R/βR182A, αI346R/αR376A, and αI348R/βR182A augmented the ATPase activity by about 70-fold from 0.07, 0.065 to 4.61, 4.97, and 4.87, respectively. Purity and integrity of α and β subunits in wild-type and mutant membrane bound F 1 F o were in excellent agreement with previously published data [8, 30]. This result also confirmed that the reduced ATPase in mutants was not due to contaminants, impaired assembly of ATP synthase, or loss of F 1 during membrane preparation, thus attributing the low mutant activities to mutant F 1 .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Double mutants αI346R/βR182A, αI346R/αR376A, and αI348R/βR182A augmented the ATPase activity by about 70-fold from 0.07, 0.065 to 4.61, 4.97, and 4.87, respectively. Purity and integrity of α and β subunits in wild-type and mutant membrane bound F 1 F o were in excellent agreement with previously published data [8, 30]. This result also confirmed that the reduced ATPase in mutants was not due to contaminants, impaired assembly of ATP synthase, or loss of F 1 during membrane preparation, thus attributing the low mutant activities to mutant F 1 .…”
Section: Resultssupporting
confidence: 91%
“…In previous studies, both membrane bound F 1 F o and purified F 1 preparations provided equivalent assay results [5, 8, 9, 14, 15, 30, 3235]. Therefore, all the inhibition assays in this study were carried out using membrane bound F 1 F o because it is convenient and less time consuming.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cell wall structure-related effect may explain a higher antibacterial efficacy of our N. sativa seed oil extract on Gram positive bacteria than Gram negative bacteria. In addition, inhibition of cell wall synthesis gene expression was also reported to cell wall integrity, inhibition of ATP production and cell growth were as also reported due to the phenolic content of DLBS1355 45 . Facing the multi-drug resistant pathogenic bacteria, discovery and development of new antimicrobial agents have already become a global concern.…”
Section: Discussionmentioning
confidence: 70%
“…Reactions were found to be linear with time and protein concentration. SDS-gel electrophoresis (10% acrylamide) and immunoblotting with rabbit polyclonal anti-F 1 -α and anti-F 1 -β antibodies was used to check the integrity and purity of protein [40]. …”
Section: Methodsmentioning
confidence: 99%